Accessing International Climate Change Related Finance in Latin America and the Caribbean - World Bank (Washington, DC, 2013)
Financing projects and programs to mitigate impacts of, and adapt to, the climate change is a matter of necessity not choice. This green expenditure policy note looks at factors facilitating the access to international financial instruments for Latin America and the Caribbean (LAC) countries that support mitigation of and adaptation to climate change. This policy note explores two questions: (i) does the quality of government institutions matter for enabling action aimed at mitigation or adaptation to the climate change?; and (ii) what financial instruments are available to governments in addition to own resources to address climate change challenges? This policy note aims to present them with advice on how to achieve greater access to international financing or co-financing of projects supporting renewable and alternative energy generation for transport, agriculture, housing, preservation of unique ecosystems, and other projects supporting sustainable development. This policy note describes the climate challenges facing the LAC region and then discusses the various climate financing flows. It discusses the factors affecting LAC countries' access to climate financing, and how countries can apply to several of the principal global and regional climate funds. The objective is to disseminate knowledge that will help governments of all LAC countries, and particularly finance ministries, understand and access new climate funds and financing mechanisms. The policy note consists of three parts: part one reviews the global landscape of the climate change financing for mitigation and adaptation and emerging trends, identifies various financial instruments, and presents an overview of the LAC's share of available finances from several public financing sources, both bilateral and multilateral. Part two reviews two case studies for Bolivia and El Salvador that demonstrate how each of these countries addresses environmental challenges through its policies, institutional systems and involvement of the civil society. Part three includes technical annexes, which represent a compilation of technical information presenting main climate change financial instruments. A list of global and specialized climate funds of possible interest to LAC countries appear in annex one. A complementary list of climate finance instruments appears in annex two, in which climate funds as well as financial tools are named, described, and categorized according to their primary purpose. A more detailed description of several of the largest climate funds including when such funds were founded, their purpose, and eligibility requirements are presented in annex three. Annex four provides a step-by-step description of how to apply to the largest climate funds. Annex five lists the LAC projects that have been supported by Global Environment Facility (GEF) by country.